Distribution of sea urchin barrens in shallow algal communities along the eastern Adriatic coast - CVITKOVIĆ, IVAN; DESPALATOVIĆ, MARIJA; ŽULJEVIĆ, ANTE; VUČIĆ, IVAN; LUČIĆ, PETRA; NEJAŠMIĆ, JELENA (Mediterranean Marine Science, 2024)
The sea urchins Paracentrotus lividus and Arbacia lixula are important herbivores in algal communities of the infralittoral rocky bottoms in the Mediterranean Sea. However, grazing by sea urchins that outweighs natural algal recruitment processes might result in the formation of barrens, which are areas dominated by urchins and coralline algae. We present the results of the first large-scale mapping of sea urchin barrens and analyses of sea urchins’ impact on the main algal communities across 1955.5 km of rocky coastline on the eastern side of the Adriatic Sea (Croatia). Since mapping was performed over a geographically wide area and covered a representative quantity of approximately 40% of the coastline of the central part of the Adriatic Sea, the results could be considered to reflect the general situation in that area of the eastern Adriatic coast. Mapping revealed that sea urchin barrens are present along over 35% of the coastline, while the complete absence of algal cover was recorded in 8% of the inspected area. Communities with canopy-forming algae, which are the most valuable shallow-water communities of the Mediterranean Sea, represent the largest proportion of the observed coastline and are affected by sea urchins in over 28% of their extent. Among other factors, the extensive harvesting of date mussels (Lithophaga lithophaga) in the 1970s, 1980s, and early 1990s is likely one of the main activities that resulted in exceptional sea urchin expansion via the removal of micropredators and establishment of shelters for subadult urchins.